Business Plan Design for a Culinary MSME: A Case of Mojo 94 Catering - Rahmadian, Reihan; Ismail, Taufiq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This qualitative research aims to design business development strategies for Mojo 94 Catering, a local catering business in Batu City that still relies on word-of-mouth promotion and lacks a structured financial system. By applying market penetration and market development strategies, this study seeks to identify market expansion opportunities through social media optimization and improvements in managerial and operational systems. Data were collected through observation, interviews, and document studies. The analysis results show that implementing digital marketing strategies and improving the financial reporting structure can enhance the business's competitiveness. In addition, the financial projections indicate a positive investment feasibility, as reflected in favorable IRR, NPV, and payback period indicators. This business plan is expected to serve as a reference for Mojo 94 Catering in making strategic decisions and enhancing the long-term sustainability of the business.